Answer:
40
Step-by-step explanation:
I think but what do you mean???!!!!
Answer:
![r=\sqrt{\frac{3V}{(\pi h)}}](https://tex.z-dn.net/?f=r%3D%5Csqrt%7B%5Cfrac%7B3V%7D%7B%28%5Cpi%20h%29%7D%7D)
Step-by-step explanation:
we know that
The volume of a right circular cone is equal to
![V=\frac{1}{3}\pi r^{2}h](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B1%7D%7B3%7D%5Cpi%20r%5E%7B2%7Dh)
where
r is the radius of the base of the cone
h is the height
Solve for r-----> That means, isolate the variable r
so
step 1
Multiply by 3 both sides
![3V=\pi r^{2}h](https://tex.z-dn.net/?f=3V%3D%5Cpi%20r%5E%7B2%7Dh)
step 2
Divide by
both sides
![\frac{3V}{(\pi h)}=r^{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3V%7D%7B%28%5Cpi%20h%29%7D%3Dr%5E%7B2%7D)
step 3
take square root boot sides
![r=\sqrt{\frac{3V}{(\pi h)}}](https://tex.z-dn.net/?f=r%3D%5Csqrt%7B%5Cfrac%7B3V%7D%7B%28%5Cpi%20h%29%7D%7D)
Answer:
See below
Step-by-step explanation:
1)
![\frac{11 + x}{(2 - x)(x - 3)} = \frac{A}{2 - x} + \frac{B}{x - 3} \\ \\ \therefore \: \frac{11 + x}{(2 - x)(x - 3)} = \frac{A(x - 3) +B(2 - x) }{(2 - x)(x - 3)} \\ \\ \therefore \: 11 + x = Ax - 3A + 2B - Bx \\ \\ \therefore \: 11 + x = - 3A + 2B + Ax - Bx\\ \\ \therefore \: 11 + x = - 3A + 2B + (A - B)x \\ \\ equating \: the \: like \: terms \: on \: both \: sides \\ A - B = 1 \\ \therefore \: A = B + 1.....(1) \\ \\ - 3A + 2B = 11....(2) \\ from \: eq \: (1) \: and \: (2) \\ - 3(B + 1) + + 2B = 11 \\ \\ - 3B - 3 + 2B = 11 \\ \\ - B = 11 + 3 \\ \\ B = - 14 \\ A = - 14 + 1 = - 13 \\ \\ \frac{11 + x}{(2 - x)(x - 3)} = \frac{ - 13}{2 - x} + \frac{ - 14}{x - 3} \\ \\ \frac{11 + x}{(2 - x)(x - 3)} = - \frac{ 13}{2 - x} - \frac{ 14}{x - 3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7BA%7D%7B2%20-%20x%7D%20%20%2B%20%20%5Cfrac%7BB%7D%7Bx%20-%203%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7BA%28x%20-%203%29%20%2BB%282%20-%20x%29%20%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%20%5C%5C%20%20%5C%5C%20%5Ctherefore%20%5C%3A%20%2011%20%2B%20x%20%3D%20Ax%20-%203A%20%2B%202B%20-%20Bx%20%5C%5C%20%20%5C%5C%20%20%5Ctherefore%20%5C%3A%2011%20%2B%20x%20%3D%20-%203A%20%20%2B%202B%20%20%2B%20Ax%20-%20%20Bx%5C%5C%20%20%5C%5C%20%20%5Ctherefore%20%5C%3A%2011%20%2B%20x%20%3D%20-%203A%20%20%2B%202B%20%20%2B%20%28A%20-%20B%29x%20%5C%5C%20%20%5C%5C%20equating%20%5C%3A%20the%20%5C%3A%20like%20%5C%3A%20terms%20%5C%3A%20on%20%5C%3A%20both%20%5C%3A%20sides%20%5C%5C%20A%20-%20B%20%3D%201%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20A%20%20%3D%20%20B%20%20%2B%20%201.....%281%29%20%5C%5C%20%20%5C%5C%20%20-%20%203A%20%20%2B%202B%20%3D%2011....%282%29%20%5C%5C%20%20from%20%5C%3A%20eq%20%5C%3A%20%281%29%20%5C%3A%20and%20%5C%3A%20%282%29%20%5C%5C%20%20-%203%28B%20%20%2B%20%201%29%20%2B%20%2B%202B%20%3D%2011%20%5C%5C%20%20%5C%5C%20-%203B%20%20%20-%203%20%20%2B%202B%20%3D%2011%20%5C%5C%20%20%5C%5C%20%20-%20B%20%3D%2011%20%2B%203%20%5C%5C%20%20%5C%5C%20B%20%3D%20%20-%2014%20%20%5C%5C%20A%20%20%3D%20%20%20-%2014%20%2B%20%201%20%3D%20%20-%2013%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7B%20-%2013%7D%7B2%20-%20x%7D%20%20%2B%20%20%5Cfrac%7B%20-%2014%7D%7Bx%20-%203%7D%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B11%20%2B%20x%7D%7B%282%20-%20x%29%28x%20-%203%29%7D%20%20%3D%20-%20%20%20%5Cfrac%7B%2013%7D%7B2%20-%20x%7D%20%20%20-%20%20%5Cfrac%7B%2014%7D%7Bx%20-%203%7D)
2)
![\therefore \frac{12x + 11}{x^2 +x - 6}=\frac{A}{(x +3)}+\frac{B}{(x - 2)}](https://tex.z-dn.net/?f=%20%5Ctherefore%20%5Cfrac%7B12x%20%2B%2011%7D%7Bx%5E2%20%2Bx%20-%206%7D%3D%5Cfrac%7BA%7D%7B%28x%20%2B3%29%7D%2B%5Cfrac%7BB%7D%7B%28x%20-%202%29%7D)
Equating like terms on both sides:
Solving equations (1) & (2), we find:
A = 5, B = 7
![\therefore \frac{12x + 11}{x^2 +x - 6}=\frac{5}{(x +3)}+\frac{7}{(x - 2)}](https://tex.z-dn.net/?f=%20%5Ctherefore%20%5Cfrac%7B12x%20%2B%2011%7D%7Bx%5E2%20%2Bx%20-%206%7D%3D%5Cfrac%7B5%7D%7B%28x%20%2B3%29%7D%2B%5Cfrac%7B7%7D%7B%28x%20-%202%29%7D)
Let
x--------->number of products
y1--------> <span>the cost of producing a product
y2------> </span><span>the cost of sell a product
</span><span>
we know that
y1=120,000+20x-------> equation 1
y2=50x------> equation 2
equate equation 1 and equation 2
120,000+20x=50x
50x-20x=120,000
30x=120,000
x=4000
the answer is
4000 pieces</span>